ASAL-USUL REOG: SASTRA LISAN SINDIRAN BIROKRASI PADA MASANYA - Purnani, Siwi Tri (Universitas Negeri Surabaya, 2017)
Literature is one form of cultural for delivering all forms of initiative, work, events, and human beliefs are poured in written and non-written. Literary were created also to be used for the various purposes that people wants, to give suggestions, satire, criticism, education, and so on. This article aims to let the reader understand that one of the examples of oral literature that was also created with the sarcasm is the story of the origin of Reog. There is one version that spread in the many peopleand has links with the political bureaucracy of its time. At that time, Reog believed to be used as a medium or a means to convey satire and criticism of the people to the government. The sarcasm is contained in Reog?s origins with a version of the story of Ki Ageng Kutu?s rebellion, a royal servant in the Bhre Kertabhumi period, the last Majapahit king who had a power in the fifteenth century. It was told that Ki Ageng Kutu was wrathful with the influence of King?s wife who came from Cina and his corrupt government.